Preliminary report on human remains from Tell Masaikh and Tell Ashara. Season 2008 - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2013)
In the Middle Euphrates Valley, excavations are currently carried out at Tell Hariri (ancient Mari) and several sites near Tell Ashara. Our research area is Terqa and its surroundings. Terqa lies on the right bank of the Euphrates, about 60 km to the north-west from the ancient city of Mari. In 1996, excavation work was extended beyond ancient Terqa onto the area 6 km away to the north, to Tell Masaikh. Initially, it was rescue excavation, but with time it became regular archaeological work. This paper is a summary of anthropological research conducted in 2008. We have been excavated 82 human skeletons (58 individuals from Tell Masikh, and 24 from Tell Ashara).